RESPON ORGANISATION FOR ECONOMIC CO-OPERATION AND DEVELOPMENT (OECD) TERHADAP PENGGUNAAN ARTIFICIAL INTELLIGENCE (AI) DALAM PENDIDIKAN DI FINLANDIA - Fajar, Rahmad; Pahlawan, Indra (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study analyzes the role of the OECD in the implementation of AI-based learning methods in Finnish secondary schools during the 2019–2021 period. The study aims to examine the contribution of the OECD as an international organization in facilitating AI-based educational policies, analyze the implementation of OECD recommendations in Finland, and evaluate the impact of AI on the Finnish education system. This research employs a qualitative approach with a descriptive-explanatory method. Data collection techniques include literature review and document analysis, covering OECD policies and reports on AI implementation in Finland's education sector. The approach is deductive, utilizing a liberalism perspective and international organization theory to analyze the role of the OECD in assisting education through AI in Finland. The results of this study indicate that the OECD acts as an arena, actor, and instrument in promoting AI adoption in Finland through a series of policy recommendations. Finland has integrated OECD guidelines into its national curriculum, teacher training programs, and the development of adaptive learning platforms. The implementation of AI has proven to enhance personalized learning, assessment efficiency, and student engagement. However, this implementation faces challenges such as digital infrastructure gaps and the need for further teacher training. Keywords: OECD, Artificial Intelligence, Educational Policy